Analytical Evaluation of Abhraka Bhasma Samples after Marana, Amritikarana and Lohitikarana (International Journal of Ayurveda and Pharma Research, 2024)
Rasaushadhies or herbo-mineral formulations undergo rigorous processes to convert into nano size. The particle size does matters a lot in terms of absorption, assimilation and proper excretion from the body. The pharmaceutical procedures should be strictly adhered so as to ensure safety and efficacy. Abhraka bhasma is a popularly used formulation in Ayurvedic practice. Abhraka or black mica is a bad conductor of heat. So the process of Bhasmikarana requires high quantum of heat in order to render into Bhasma form. Amritikarana is a specific process included in the preparation of Abhraka bhasma. The current study evaluates the essentiality of this process in Bhasmikarana. A detailed analytical study is been carried out to find the differences in the samples before and after Amritikarana. The present study reveals that the particle size has reduced much and the iron content was at maximum concentration in the samples after the process of Amritikarana and Lohitikarana.